Decision-making patterns and self-confidence in high school adolescents - Luna Bernal, Alejandro César Antonio (2014)
The present study aimed to analyse the factor structure of the Melbourne Decision Making Questionnaire (DMQ-II), and to examine the relationships between the factors identified and Self-confidence, in order to conceptualize the decision-making process in adolescents under the Conflict Model of Decision Making. Participants were 992 Mexican high-school students, aged between 15 and 19 years. The three factors were identified as decision-making patterns in adolescents: a) Vigilance, b) Hipervigilance/Procrastination and c) Buck-passing. The Self-confidence showed a positive effect on Vigilance, and a negative effect on theother two patterns. Results are discussed considering the literature on decision making in adolescence.